Pengaruh Model Latihan Drills Under Simplified Untuk Meningkatkan Keterampilan Blocking Atlet Bolavoli Putra Kabupaten Lima Puluh Kota - Muhammad Ihsan Fajri; Muhamad Sazeli Rifki (JURNAL STAMINA, 2019)
The problem in this research is the still low blocking skills of male volleyball athletes in Lima Puluh Kota Regency. The purpose of this research was to determine the extent to which the influence of the Drills Under Simplified Conditions in improving blocking skill male volleyball athletes in Lima Puluh Kota Regency. This type of research is a quasi-experimental. The population in this research were male volleyball athletes in Lima Puluh Kota Regency which amounted to 24 male athletes. The sampling technique uses purposive sampling. Therefore the sample in this research amounted to 12 people who is actively participating in the training. To obtain data, do measurements were made on blocking using the blocking skill test or battery test. Data were analyzed by using different mean test analysis ( t test). The results of the research indicate that: There is a significant influence on the Drills Under Simplified Conditions exercise model in increasing the Blocking Skills of men Volleyball Athlete's in the Lima Puluh Kota Regency. This increase in blocking skills is equal to 7.75 which is from the average score of the initial test (Pre test) 13.92 and the final test (Post test) becomes 21.67, and to test the hypothesis obtained a value thitung 14.03 large from ttabel 1.79